Peran Guru Dalam Pembinaan Akhlak Siswa Di MDA Ar-Arsyad Kelurahan Nan Kodok Kota Payakumbuh - Lucky Ramadhan; Salmi Wati; Alimir Alimir; Pendi Hasibuan (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
The background for writing this research is because in the environment where the researchers live, many children are of poor moral character, this causes many children in the research environment to be far from religious teachings, such as not praying, not fasting, and other things that deviate from religious teachings. Even though in the researcher's environment there is a place for education, both formal and non-formal schools such as MDA. This is also due to the increasing sophistication of information and communication technology that everyone gets through their respective gadgets whether they are adults or children. Especially for children who get more negative things through these gadgets. The approach used in this study is a qualitative approach, meaning that researchers will look at phenomena that occur in society. In this study, researchers used descriptive qualitative research. The key informants in this study were TPA teachers, while the supporting informants were TPA administrators and TPA students in Nankodok Village. Research techniques to collect data used in this thesis are interviews and observation and also supported by documentation. The collected data were then analyzed using qualitative analysis techniques. The results of the study concluded that: (1) The role played by the MDA Arsyad teacher in fostering morals for his students cannot be said to be successful. Because there are still Ar arsyad students who have not implemented how to behave properly in accordance with the moral development that has been given by the teacher to students. What's more, teachers also have to be even more active in eliminating bad habits that their students get from gadgets. (2) Factors that influence teachers in fostering student morals at MDA Ar-Arsyad consist of supporting factors and inhibiting factors. Supporting factors consist of parents at home, then motivation and finally the environment. Meanwhile the inhibiting factors consisted of peers and also the mass media. Both have their own impact in the moral development carried out by the teacher.